1964
DOI: 10.1177/12.5.364
|View full text |Cite
|
Sign up to set email alerts
|

The Histochemical Demonstration of Pancreatic-Like Lipase and Comparison With the Distribution of Esterase

Abstract: A new histochemical method for lipase was developed using naphthol-AS nonanoate as a substrate and sodium taurocholate as an activator. In a comparison with esterase, pancreatic-like lipase activity was studied in various tissues. As a result, it was disclosed that the pancreatic acinar cells show the highest activation with sodium taurocholate, and lipase activity is located in the region immediately surrounding the zymogen granules and not within the granules themselves. Maximum activity of esterase and lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1964
1964
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…As ragards the esterase distribution in the epithelial cells of the small intestinal mucosa, Geyer and Nietzold (1968) who observed the guinea pig intestinal mucosa by light microscopy using naphthyl acetate as a substrate, reported that the esterase activity was intense on the striated border but rather weak in the cytoplasm of the mucosal epithelial cell. Using the same histochemical method an extremely low level of the cytoplasmic esterases has also been reported by Nachlas and Seligman (1949b) and Abe, Kramer and Seligman (1964) in the dog duodenal mucosa and guinea pig jejunum, by Chessick (1953) and Shnitka (1960) in the cat duodenal mucosa. Nachlas and Seligman (1949b) reported an absence of esterase activities in the cytoplasm of epithelial cells in the human jejunum.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As ragards the esterase distribution in the epithelial cells of the small intestinal mucosa, Geyer and Nietzold (1968) who observed the guinea pig intestinal mucosa by light microscopy using naphthyl acetate as a substrate, reported that the esterase activity was intense on the striated border but rather weak in the cytoplasm of the mucosal epithelial cell. Using the same histochemical method an extremely low level of the cytoplasmic esterases has also been reported by Nachlas and Seligman (1949b) and Abe, Kramer and Seligman (1964) in the dog duodenal mucosa and guinea pig jejunum, by Chessick (1953) and Shnitka (1960) in the cat duodenal mucosa. Nachlas and Seligman (1949b) reported an absence of esterase activities in the cytoplasm of epithelial cells in the human jejunum.…”
Section: Discussionsupporting
confidence: 57%
“…Since then, contributions have been made in the field of nonspecific esterase histochemistry for the development of azo dye technique by Nachlas and Seligman (1949a, b), Gomori (1952), Chessick (1953), Malaty and Bourne (1955), Shnitka (1960), Padykula, Strauss, Ladman and Gardner (1961), Abe, Kramer and Seligman (1964), Friedman, Strachan and Dewey (1966), and Geyer and Nietzold (1968). Barrnett (1952a, b) introduced indoxyl acetate as a substrate for the enzyme reaction.…”
mentioning
confidence: 99%
“…In the latter substitution of the fast blue B coupler with hexazonium pararosanilin (Barka & Anderson, 1963) gave better results, which were further improved by reducing the amount of coupler to one-quarter of the specified quantity. Methods to demonstrate lipases included the Tween 80 (Gomori, 1952) and naphthol-AS-nononoate (Abe et al, 1964) techniques.…”
Section: Methodsmentioning
confidence: 99%
“…At the light microscopic level, pancreatic lipase has been localized around the zymogen granules in the apical portion of the acinar cells by use of the histochemical technique (1,20). Seligman et al (36), who used an aromatic thioester of nonanoic acid as a substrate, have shown with light and electron microscopy that lipase did not localize inside the zymogen granule but was present on the outer surface of the zymogen granule.…”
Section: Discussionmentioning
confidence: 99%
“…has been studied by many investigators with the histochemical method (1,9,10,20,23,24,36), and with the biochemical method (3,4,6,8,12,39).…”
mentioning
confidence: 99%